Ketahanan Pangan untuk Menjaga Nutrisi Keluarga di Desa Melinggih Kelod Payangan Gianyar - Rima Kusuma Ningrum; I Made Kawan; Adi Pratama Putra (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Food security is a condition of sufficient food availability, not only the availability of food at the regional level but also at household and individual levels to maintain nutrition. During the COVID-19 pandemic, people must be able to maintain their health by fulfilling the nutrients needed. Nutrients contained in food need to be maintained by good food processing. By having good knowledge of food processing, partners are expected to be able to provide good nutrition for all family members. This COVID-19 pandemic, the community is not only experiencing difficulties in the health sector but also experiencing difficulties in the economic field, with the holding of assistance in food management and security, the community will be equipped with knowledge on how to maintain food security by cultivating freshwater fish. Partners of this program are families who have been accompanied by medical students in the COME 1000 HAK Program with a total of 10 families. Each KK is accompanied by one student. This community service team provided assistance in the form of tarpaulin ponds, freshwater fish seeds and fish feed. In this service, the team collaborates with teams from Fishery Study Program, as resource persons on how to keep good fish to get optimal results. With this program, it is hoped that the community will have food security and process it properly which can meet the nutritional needs of the family.